Amsterdam coffeeshops, victimisation, and police mobilization. (9th August 2021) - Moeller, Kim; Jacques, Scott
ABSTRACT: Police mobilisation is a first step in the judicial process and an important source of information on offending. Whether victims mobilise police is affected by their assessment of its utility. Victims who are criminals, such as drug dealers, are known to face a different cost–benefit scenario than law-abiding persons. Dutch 'coffeeshops' are a unique type of dealer. They operate in a grey area, allowed by the government to sell a prohibited drug, cannabis, so long as they comply with a set of regulations. Little is known about their mobilisation of police in response to victimisation, including how it is affected by the rules governing their business. We explore this issue with qualitative data collected from personnel of 50 coffeeshops in Amsterdam, the Netherlands. We analyse how they think about the potential benefits and costs of asking the police for help post victimisation. In many ways, their thought process is similar to that of most any victim, but they also consider the potential negative ramifications of inviting police to their door. We conclude by discussing the implications for future research, regulation and drug control broadly, and coffeeshops specifically.